2023
DOI: 10.56053/7.2.325
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer in copper oxide nanostructure

Abstract: The deposition potential affects the structural, morphological, optical, and electrochemical impedance spectroscopy properties of cuprous oxide (Cu2O) thin films formed on copper (Cu) substrates adopting a three-electrode electrochemical deposition procedure. XRD data revealed that the deposited films have a cubic structure established with desired (111) growth orientation. Scanning electron microscopy (SEM) images reveal that Cu2O film has very well three-sided pyramid-shaped grains which are equally spread o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…To reduce the cost without compromising the catalytic capabilities, attempt has been made to synthesize ruthenium (Ru) with other transition metal based oxides as electro-catalysts for HER and OER [ 6 , 14 ]. In literature, there are numerous techniques, such as solid-state method, hydrothermal method, sol-gel method and deposition method, available to synthesize various oxide materials and it was found that the synthetic method and the curing temperature have profound effect on the crystal growth and hence on their catalytic properties [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. Recent report on the low cost synthesis of bimetallic oxides and its coatings over a metal surface shows the hard-corrosion resistance property [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the cost without compromising the catalytic capabilities, attempt has been made to synthesize ruthenium (Ru) with other transition metal based oxides as electro-catalysts for HER and OER [ 6 , 14 ]. In literature, there are numerous techniques, such as solid-state method, hydrothermal method, sol-gel method and deposition method, available to synthesize various oxide materials and it was found that the synthetic method and the curing temperature have profound effect on the crystal growth and hence on their catalytic properties [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. Recent report on the low cost synthesis of bimetallic oxides and its coatings over a metal surface shows the hard-corrosion resistance property [ 34 ].…”
Section: Introductionmentioning
confidence: 99%